Effects of anthropogenic electromagnetic fields used for subsurface oil and gas exploration (controlled-source electromagnetics, CSEM) on the early development of Atlantic haddock (Melanogrammus aeglefinus) - Guillebon, Claire; Perrichon, Prescilla; Browman, Howard I.; Cresci, Alessandro; Sivle, Lise Doksæter; Skiftesvik, Anne Berit; Zhang, Guosong; Durif, Caroline M.F. (Marine pollution bulletin, 2025)
Controlled source electromagnetics (CSEM) uses electromagnetic fields (EMF) to detect oil reservoirs. Atlantic haddock, Melanogrammus aeglefinus, is a commercially important demersal fish species that can potentially be impacted by such surveys due to potential overlap with egg distribution. In this study, haddock eggs were exposed to EMF, replicating CSEM survey conditions in a laboratory. Three different EMF intensities were used to replicate different distances between the EMF source and the organism. Exposures lasted for 15 min. A worst-case scenario, i.e. 1 h exposure at the highest EMF level was also carried out. None of the treatments caused malformations, mortality or affected hatching of eggs. However, EMF exposure induced tachycardia in newly hatched larvae and reduced the size of their yolk sac reserve. The effect was significant at the lowest EMF intensity (corresponding to 1000 m between the EMF source and the exposed subject) and increased with exposure time and intensity. •CSEM methods generates electromagnetic fields to map the presence of oil reservoirs.•Electromagnetic field exposure had no impact on embryo mortality of Atlantic haddock.•The absorption of the yolk sac was faster after electromagnetic field exposure.•Embryos exposed to CSEM-generated electromagnetic field exhibited tachycardia.